The influence of sustainable packaging on brand perception in fast-moving consumer goods : Comparing perceptions of international consumers - Björklund, Anna (My University, 2020)
Packaging holds a number of benefits, including its ability to protect products through transportation and its ability to convey the brand and usage of the product. Although most materials used in packaging can be recycled, a great amount cannot, and the production, use, disposal and recovery of packaging not only create substantial amounts of waste, but they also consume raw materials and energy. A way to lower one’s environmental impact is by preferring sustainable packaging, which is packaging that is effective, efficient, recyclable and safe. However, a number of external factors influence our likelihood to behave sustainably, including our psychological capabilities and cultural conventions. The objective of this thesis is to gather a better understanding of what the factors are that influence consumer behaviour in relation to sustainable packaging. A quantitative approach using survey questionnaire was chosen for this thesis as it was seen as the best method for gaining insight on attitudes and the relationships between constructs. The theory of planned behaviour (TPB) in combination with the norm activation model (NAM) were used to formulate the conceptual framework of the study and the survey questions. Statistical analysis was employed to examine the responses gathered with the survey questionnaire. The results of the study supported previous research as both the TPB and NAM constructs were found to predict intention and, perpetually, sustainable consumer behaviour, while neither the brand of the product nor the cultural background of the respondent could be found to influence either. Respondents generally had very positive attitudes towards sustainability, however, this was not visible in their behavioural preferences suggesting an attitude-behaviour gap. Respondents were also somewhat unsure of what constituted as sustainable and viewed informativity as the most important aspect of packaging. One of the key challenges for managers, markets and designers of sustainable packaging is to develop packaging designs that are not only sustainable but also accepted by consumers as different materials communicate different levels of sustainability to different people. Further, packaging should be able to evoke positive emotions in consumers while retaining its functional properties.
Keywords: Sustainable packaging, consumer behaviour, theory of planned behaviour, norm activation model, brand perception